Hadith on Tabarruj: Relevance and Limitations of Makeup Use for Muslim Women in the Contemporary Era - Rahmi, Tutia; Nazmi, Khairin; Siregar, Rois Hamid; Harahap, Alwi Padly (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Tabarruj, in the context of Islamic teachings, refers to the actions of women who display their beauty or private parts with the aim of attracting the attention of the opposite sex. Hadiths related to tabarruj are often used as a reference to limit the use of makeup and jewelry for Muslim women. However, along with the times and cultural changes, this issue has become increasingly relevant to discuss, especially regarding the limitations of using makeup in the contemporary era. This research aims to analyze the relevance of the hadith regarding tabarruj in the context of modern Muslim society, as well as providing views regarding the limitations of using makeup for Muslim women from an Islamic perspective. The method used is a literature review with a thematic analysis approach to hadiths related to tabarruj. The research results show that although the use of makeup is not completely prohibited, there are still limitations, namely not excessively and not aiming to attract the attention of the opposite sex beyond what is required by the Shari'a. In conclusion, Muslim women can use makeup within reasonable limits, in accordance with the principle of simplicity and not violating Islamic teachings about aurat and tabarruj. It is hoped that this research will provide insight for Muslims in understanding the relationship between religious teachings and social practices in the modern era.